Exploring the job resources experienced by employees with hearing impairment in South Africa - Strauss Chelius; Bouwer E. Jonker; Marissa Brouwers (SA Journal of Human Resource Management)
Orientation: The United Nations Agenda of Sustainable Development Goal (SDG) number 8, and specifically target 8.5, highlights the employment of people with disabilities (PWD). The current study sheds light on job characteristics that employees with hearing impairments (EwHIs) experience as job resources.